Predicting Accrual Achievement: Monitoring Accrual Milestones of NCI-CTEP Sponsored Clinical Trials - Cheng, Steven K. (2011)
BACKGROUND: The need to increase the number oncology clinical trials with sufficient enrollments is a well-known issue particularly for trials targeting therapeutic applications. It is critical to identify early predictors of eventual study accrual achievement. METHODS: All non-pediatric, phase I, I/II, II, and III therapeutic studies supported by the National Cancer Institute-Cancer Therapy Evaluation Program between 2000–2007 (n=764) were analyzed for accrual performance. Accrual achievement is defined as those enrolling 100% or more of the stated minimum accrual goal at the time of trial closure. Two accrual milestones were analyzed per trial: time-to-first patient enrollment and expected-time-to-accrual. Multivariate-logistic regression analysis was used to calculate the odds ratio with respect to the likelihood of clinical trial accrual achievement. RESULTS: A total of 81.5 percent (n=623) of the trials did not achieve projected accrual goals within the anticipated accruing period. Furthermore, 37.2 percent (n=284) of trials failed to achieve the minimum projected accrual at study closure regardless of time the trial was open. Trials that accrue the first enrollment beyond two months (n=379,49.6%) are significantly less likely to achieve accrual performance than those trials that enroll patients under two months (odds ratio:0. 637,95% CI:0.464–0.875, p=0.005). Of the studies that are open beyond the anticipated enrollment period (n=603), those do not achieve at least 60.0% of the projected minimum accrual (n=391,64.8%) have a significantly less likelihood of achieving final accruals by study closure (odds ratio; 0.190,95% CI:0.055–0.652, p=0.008). CONCLUSIONS: The time-to-first-patient enrollment as well as expected-time-to-accrual is shown to be valid measures to evaluate likelihood of achieving minimum projected accrual.